Analysis of Work Motivation of Educators at SMK Al-Huda Sariwangi with Maslow's Hierarchy of Needs Approach - Fida Fadilatul Romdoniyah; Mulyawan Safwandy Nugraha (Sustainable, 2024)
This study analyzes educators' work motivation at SMK Al-Huda Sariwangi using Maslow's Hierarchy of Needs, focusing on five basic needs: physiological, security, social, appreciation, and self-actualization. The research employs a quantitative-descriptive method with interviews and observations involving the principal and educators. Findings indicate that SMK Al-Huda generally fulfills educators' motivational needs: compensation and work environment are satisfactory, job security and health benefits are adequate with some room for improvement, social relationships are harmonious, recognition is provided but can be enhanced, and self-actualization is supported through training opportunities. Despite these successes, further improvements are needed, and future studies should include comparisons across multiple schools for broader insights.